36.0k views
4 votes
What is the solution to 5a+6 -4a=2(a-4)

2 Answers

4 votes

Answer:

14=a

Explanation:

5a+6 -4a=2(a-4)

Distribute 2

5a+6 -4a= 2a-8

Use commutative property

(5a-4a= a)

a+6=2a-8

a-a+6=2a-a-8

6=a-8

6+8=a-8+8

14=a

(I hope I wrote my equations correctly so that they are not confusing sorry)

User StackExchange User
by
5.4k points
7 votes

What is the solution to 5a+6 -4a=2(a-4)

Answer:

Solve for A by simplifying both sides of the equation, then isolating the variable.

a=14

User Tourki
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.